Siagonodon Borrichianus (Degerbol's Blind Snake): Avian predation - Martínez, Tomás Agustín (2019)
Siagonodon Borrichianus is a small snake leptotyphlopid snake (ca. 280 mm total lenght) that is distributed throught the western and southern areas of Monte phytogeographic region including La Rioja, Mendoza, Rio Negro and San Juan provinces, Argentina (Perez et al. 2010. Herpetol. Notes 3:62-67). The species appears to be rare and is known from only a few localities. Here, we report the first observation of predation on S. borrichianus by the Burrowing Owl (Athene cunicularia).